Fit Kids, Bad Grades: You're Doing Fitness Assessment All Wrong!. Issue 2 (12th February 2022) - Johnson, Ingrid L.; Armstrong, Tess; Lewis, Colleen
Abstract: This article focuses on the premise that the purpose of physical education is not to produce elite athletes or focus solely on fitness, but rather provide students with the tools and experiences to help them become fit, to their best ability, across their lifespan. It argues that teachers should never grade students on their actual fitness performance.